2019
DOI: 10.1108/jd-11-2018-0178
|View full text |Cite
|
Sign up to set email alerts
|

Reading practices in scholarly work: from articles and books to blogs

Abstract: Purpose The purpose of this paper is to examine the role of reading in scholarly work among academics in Finland. This study analyzes readings from a variety of publication types including books, conference proceedings, research reports, magazines, newspapers, blogs, non-fiction and fiction. Design/methodology/approach An online survey was developed and distributed in Finland in 2016–2017 (n=528). Participants were asked their finding and use of scholarly information resources of all types. Findings Schola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
1
10
0
2
Order By: Relevance
“…Our results also suggest that students make use of the older articles more often than other users, especially researchers. This is consonant with findings of a study regarding the reading patterns of Finnish scholars, according to which 'doctoral students and postdocs use more articles published more than five years ago' (Late et al, 2019).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results also suggest that students make use of the older articles more often than other users, especially researchers. This is consonant with findings of a study regarding the reading patterns of Finnish scholars, according to which 'doctoral students and postdocs use more articles published more than five years ago' (Late et al, 2019).…”
Section: Discussionsupporting
confidence: 83%
“…A recent study on reading practices in Finnish academia points to PhD students and professors as the most frequent users of journal articles, and the articles were almost always accessed electronically (with the exception of humanities scholars who still read printed journals). Moreover, scholars were mainly interested in recent publications, and this was especially noticeable in the case of journal articles (Late et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Publishing practices in humanities and social sciences favour national publishing while publishing in, for example, natural sciences and medicine is focused on international publications (Kulczycki et al ., ; Kyvik, ). Scholars also read more national publications in humanities and social sciences (Late, Tenopir, Talja, & Chirstian, ). This is explained with lower degree of mutual dependence between scholars in social sciences and humanities (Whitley, ).…”
Section: Discussionmentioning
confidence: 99%
“…A nationwide research conducted by Late et al (2019) in Finland reported reading practices among scholars. Scholars were found reading books, blogs, conference proceedings, research reports, magazines and newspapers with differences in disciplines, ranks, work responsibilities and type of research performed.…”
Section: Reading Knowledge Sourcesmentioning
confidence: 99%